A test for a difference in the associability of blocked and uninformative cues in human predictive learning. Issue 2 (February 2019) - Uengoer, Metin; Dwyer, Dominic M; Koenig, Stephan; Pearce, John M
In human predictive learning, blocking, A+ AB+, and a simple discrimination, UX+ VX–, result in a stronger response to the blocked, B, than the uninformative cue, X (where letters represent cues and + and – represent different outcomes). To assess whether these different treatments result in more attention being paid to blocked than uninformative cues, Stage 1 in each of three experiments generated two blocked cues, B and E, and two uninformative cues, X and Y. In Stage 2, participants received two simple discriminations: either BX+ EX– and BY+ EY–, or BX+ BY– and EX+ EY–. If more attention is paid to blocked than uninformative cues, then the first pair of discriminations will be solved more readily than the second pair. In contrast to this prediction, both discriminations were acquired at the same rate. These results are explained by the theory of Mackintosh, by virtue of the assumption that learning is governed by an individual rather than a common error term.